An exploratory study of the development and usability of a new type of experiencing scale - Joo, Eun Sun; Shin, Seol Ae; Kim, Joo Young; Ahn, Ho Won; Kim, Byung Sun (Edelweiss Applied Science and Technology, 2025)
In psychotherapy, the best way to identify client change is to measure the client's experience within the psychotherapy session. This study was set out to develop a new type of client experience scale and to empirically validate the applicability of the new response scheme and method. The results show that this new client experience scale can be a useful tool for therapy, which is the goal of any psychotherapy or counseling, and it provides two important pieces of information: the effectiveness of the therapy and clues to improve the effectiveness of the therapy. The Client Experience Scale is therefore very promising and has the advantage that by answering the items on the scale, the client can learn about the actual likelihood of change and form a framework for evaluating the counseling and the client's own experience. In addition, by answering the scale, the client can observe his or her own psychological and physical state, which helps to solve real problems.